1999
DOI: 10.1128/jcm.37.6.1932-1934.1999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Nucleic Acid Amplification Methods for Direct Detection of Mycobacterium tuberculosis Complex in Respiratory Specimens

Abstract: Two hundred thirty respiratory specimens from 230 patients were analyzed by using COBAS AMPLICOR PCR, Amplified Mycobacterium tuberculosis Direct Test, and ligase chain reaction methods. Results were compared with those of smear microscopy and radiometric culture (Bactec) methods. No significant differences were observed among the results of the three methods, which are acceptable for direct detection of M. tuberculosis complex in respiratory specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 24 publications
5
9
0
2
Order By: Relevance
“…No significant differences in sensitivity between respiratory and extrapulmonary specimens were observed. Data from the literature about AMPLICOR sensitivity and specificity are in agreement with our findings (Bodmer et al [1], 92.6 and 99.6%; Rajalahti et al [8], 83 and 99%; Wang and Tay [10], 96.1 and 100%; and Reischl et al [9], 83.5 and 98.8%, respectively) and document that the automated AMPLICOR assay exhibits higher sensitivity and specificity than those obtained by the manual version (7).…”
Section: Discussionsupporting
confidence: 92%
“…No significant differences in sensitivity between respiratory and extrapulmonary specimens were observed. Data from the literature about AMPLICOR sensitivity and specificity are in agreement with our findings (Bodmer et al [1], 92.6 and 99.6%; Rajalahti et al [8], 83 and 99%; Wang and Tay [10], 96.1 and 100%; and Reischl et al [9], 83.5 and 98.8%, respectively) and document that the automated AMPLICOR assay exhibits higher sensitivity and specificity than those obtained by the manual version (7).…”
Section: Discussionsupporting
confidence: 92%
“…Most studies comparing different commercial amplification kits for the rapid identification of MTB report no significant differences in test performance. 9,[23][24][25][26][27][28][29][30] The overall sensitivity of the AMPLI-COR assay in this study was low (culture, 61%; clinical PTB, 44%) but was within the range of 33 to 87% reported in the literature for smear-negative PTB. 23,27,30 -34 It is higher than the sensitivity of 37% reported by Al-Zahrani et al 35 in a prospective study of 357 patients suspected of having smear-negative PTB using an in-house PCR.…”
Section: Discussionsupporting
confidence: 42%
“…In the evaluation of the E-MTD, sensitivity of 92-100 and 78-100% of specificity have been shown (Wang and Tay 1999;Scarparo et al 2000;Soini and Musser 2001). Sensitivity values of 95AE4-98AE9% and specificity of 90AE9-100% were found for the Amplicor test (Bergmann and Woods 1996;Reischl et al 1998;Wang and Tay 1999;Scarparo et al 2000;Soini and Musser 2001). The present study demonstrated that the triplex PCR kit is comparable to these two commercially available kits for the diagnosis of tuberculosis in smear-positive respiratory specimens.…”
Section: Discussionsupporting
confidence: 57%
“…For this purpose, two commercial NAA methods were launched, and their performance is quite good in smear-positive specimens. In the evaluation of the E-MTD, sensitivity of 92-100 and 78-100% of specificity have been shown (Wang and Tay 1999;Scarparo et al 2000;Soini and Musser 2001). Sensitivity values of 95AE4-98AE9% and specificity of 90AE9-100% were found for the Amplicor test (Bergmann and Woods 1996;Reischl et al 1998;Wang and Tay 1999;Scarparo et al 2000;Soini and Musser 2001).…”
Section: Discussionmentioning
confidence: 92%